PROBLEM BASED LEARNING MODEL TO EXPLORE VALUE OF LOCAL WISDOM IN SD SOCIAL STUDIES LEARNING - Faridillah Fahmi Nurfurqon; Muhammad Rizal Fauzi; Galih Dani Septian Rahayu (JMIE (Journal of Madrasah Ibtidaiyah Education), 2022)
This local wisdom-based learning is expected to be able to bridge students to understand and know the customs, culture, values and norms that apply in the region or ethnic group. This study aims to explore the values of local wisdom in elementary social studies learning using a Problem based learning model. The research design uses a descriptive research model. The data collected in the form of quantitative data through formative tests, analysis of observation sheets, and document analysis. The number of research subjects consisted of 35 students divided. This research was conducted in a public school located in Cimahi City. The results of the study indicate that the implementation of the PBL model to explore the values of local wisdom in elementary social studies learning can be selected and used as one of the appropriate methods or innovations to be applied by teachers in the online learning process.